Stochastic Dominance in Human Capital - Eden, Benjamin (Journal of Political Economy, 1980)
The paper considers the choice between two finite income paths that are subject to random variations. It is shown that if one income path, X, has more cumulative variation at the outset and less variation toward the end than another income path, Y, then X dominates Y in the sense that (almost) every decision maker prefers X to Y. The intuitive reasoning is that a decision maker with income path X can, by engaging in a fair gamble, create the random variation of the cumulative income under Y and still have the advantage that more of the uncertainty is resolved at an earlier stage.